E-finance in the Philippines: Status and prospects for digital financial inclusion - Gilberto M. Llanto; Maureen Ane D. Rosellon; Ma. Kristina P. Ortiz (Philippine Institute for Development Studies (PIDS), 2018)
Digital technology applied to banking and financial transactions or e-finance in general has made financial services more widely available and affordable to consumers. And with appropriate and affordable technologies and applications, the financially excluded and the unserved can participate in mainstream banking and finance that will open many opportunities for consumption smoothing and investment and earning possibilities. This paper attempts to study the contribution of technology towards financial inclusion in the Philippines and analyze whether e-finance has enabled the last mile consumers to avail of financial products and services affordably and conveniently. It uses data from financial inclusion databases, and results from a national financial inclusion survey, key informant interviews and focus group discussions with users of a mobile banking application. Electronic money transfers are found to be increasing in the country, but digital adoption rate, particularly for mobile payments, is relatively low especially if compared with countries in the region. The study probes into the experience and concerns of digital finance users, and presents recommendations to improve provision and use of digital financial products and services.
Keywords: 330; e-finance; digital finance; digital financial inclusion; mobile banking; electronic banking; electronic money; e-money